Inhibitory effect of sulfated galactans from the marine alga Bostrychia montagnei on herpes simplex virus replication in vitro - Duarte, M.E.R. (2001)
Sulfated polysaccharides exhibit many biological properties such as antiviral and anticoagulant activities. Herein, we report the antiviral activity of sulfated galactans extracted from the red sea-weed Bostrychia montagnei against herpes simplex virus types 1 (strain F and the thymidine kinase-deficient strains Field and B2006) and 2 (strain G). Two crude extracts obtained with cold and hot water as well as some fractions obtained by anion exchange chromatography, inhibited significantly the replication of the different strains of herpesviruses as determined by plaque reduction assays. The inhibitory effect of the compounds studied here took place only when they were added during the adsorption period. They were found to be highly selective antiviral substances, causing no impairment of Vero cell viability. Furthermore, they had no direct inactivating effect on virions by incubation in a virucidal assay. The antiviral activity could be correlated with the molecular weight and sulfate content of the polysaccharides. Although sulfated polysaccharides are generally endowed with anticoagulant properties, the results of the activated partial thromboplastin time and the thrombine time assays indicated that the natural sulfated polysaccharides from Bostrychia montagnei have very low anticoagulant activity, confirming that there is no relation between the antiviral and anticoagulant properties.